2022
DOI: 10.1088/1755-1315/1060/1/012041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spraying Some Nano-Fertilizers and Their Combinations on the Growth and Yield of Fenugreek (Trigonella foenum-graecum L.)

Abstract: The experiment was conducted in one of the special fields for the winter agricultural season 2020/2021 in Al-Qadisiyah province / Sumer-Al-Barakat sub-district, which is 17 km from the district, at 32.14 degrees north latitude and 44.99 degrees east longitude. To know the effect of spraying some nano-fertilizers and their combinations on the growth and yield of the fenugreek, the experiment was carried out according to a randomized complete block design with three replications. The experiment included 10 treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(6 reference statements)
1
0
0
Order By: Relevance
“…Likewise, on sage plants, it has been reported that the foliar spray of Si or nitric oxide, and particularly their combinations, restored chlorophyll in leaves that improved photosynthesis and consequently enhanced the shoot biomass of Cu-stressed plants [ 54 ]. Our results resemble those of Al-Saidi et al [ 55 ]. The authors showed that treating fenugreek plants with 200 kg/ha NPK (20:20:20) + 2 g/L nanoelements (B 0.5%; Mo 0.5%, Cu 0.5%, Zn 1.5%, Mg 1.5%, and Fe 8%) + nano seaweed extract at 2 g/L resulted in the highest values of vegetative growth traits relative to the control.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, on sage plants, it has been reported that the foliar spray of Si or nitric oxide, and particularly their combinations, restored chlorophyll in leaves that improved photosynthesis and consequently enhanced the shoot biomass of Cu-stressed plants [ 54 ]. Our results resemble those of Al-Saidi et al [ 55 ]. The authors showed that treating fenugreek plants with 200 kg/ha NPK (20:20:20) + 2 g/L nanoelements (B 0.5%; Mo 0.5%, Cu 0.5%, Zn 1.5%, Mg 1.5%, and Fe 8%) + nano seaweed extract at 2 g/L resulted in the highest values of vegetative growth traits relative to the control.…”
Section: Discussionsupporting
confidence: 92%